The prothrombotic state in atrial fibrillation: pathophysiological and management implications. Issue 1 (2nd November 2018) - Khan, Ahsan A; Lip, Gregory Y H
Abstract: Atrial fibrillation (AF) is the commonest sustained cardiac arrhythmia and is associated with significant morbidity and mortality. There is plenty of evidence available to support the presence of a prothrombotic or hypercoagulable state in AF, but the contributory factors are multifactorial and cannot simply be explained by blood stasis. Abnormal changes in atrial wall (anatomical and structural, as 'vessel wall abnormalities'), the presence of spontaneous echo contrast to signify abnormal changes in flow and stasis ('flow abnormalities'), and abnormal changes in coagulation, platelet, and other pathophysiologic pathways ('abnormalities of blood constituents') are well documented in AF. The presence of these components therefore fulfils Virchow's triad for thrombogenesis. In this review, we present an overview of the established and professed pathophysiological mechanisms for thrombogenesis in AF and its management implications.